Medicaol, a strigolactone identified as a putative didehydro-orobanchol isomer, from Medicago truncatula. (March 2015) - Tokunaga, Tamami; Hayashi, Hideo; Akiyama, Kohki
Graphical abstract: The main strigolactone produced by the model legume Medicago truncatula was isolated and identified. Highlights: A putative didehydro-orobanchol isomer was isolated from Medicago truncatula . This strigolactone, named medicaol, has a seven-membered ring in the A-ring part. Medicaol induced short tertiary hyphae in an AM fungus Gigaspora margarita . Plausible biosynthetic pathways for medicaol are proposed. Abstract: A major strigolactone produced by the model legume Medicago truncatula (barrel medic) has been tentatively identified as a didehydro-orobanchol isomer. In this study, a putative didehydro-orobanchol isomer was isolated from root exudates collected from barrel medic grown hydroponically under phosphate-starved conditions. The structure and absolute configurations of this strigolactone, named medicaol, were determined by a combination of spectroscopic analysis and spectral comparison with 4-deoxymedicaol which was synthesized using solvolysis and rearrangement of hydroxymethylhexahydroindenone to tetrahydroazulenone as a key step. Medicaol has a seven-membered cycloheptadiene in the A ring instead of a typical six-membered cyclohexene. Medicaol and 4-deoxymedicaol showed activity comparable to their corresponding six-membered A ring relatives, orobanchol and 4-deoxyorobanchol ( ent -2′- epi -5-deoxystrigol), in inducing hyphal branching of germinating spores of an arbuscular mycorrhizal fungus Gigaspora margarita . Plausible biosynthetic pathways from 4-deoxyorobanchol to medicaol are also proposed.